Review of the tribe Anerastiini (Lepidoptera: Pyralidae: Phycitinae) from Ukraine - Bidzilya, Oleksiy; Budashkin, Yuriy; Yepishin, Viktor (Zootaxa, 2020)
Five species of the tribe Anerastiini from Ukraine are reviewed. Coenochroa ablutella (Zeller, 1839) is reported from Ukraine for the first time. Hypsotropa limbella Zeller, 1848 is removed from the list of Pyralidae of Ukraine as it was based on a misidentification. Five new synonyms are established: Hafisia Amsel, 1950 syn. nov. of Zophodiodes Ragonot, 1887; Hafisia lundbladi Amsel, 1950 syn. nov. of Zophodiodes leucocostella Ragonot, 1887; Anerastia korbi Caradja, 1910 syn. nov. of Coenochroa ablutella (Zeller, 1839), Anerastia dubia Gerasimov, 1928 syn. nov. of Anerastia lotella (Hübner, [1813]), Peoria palaearctella (Turati, 1917) syn. nov. of Peoria incarnata (Staudinger, 1879) comb. nov. The females of C. ablutella and Z. leucocostella are described for the first time. Adults and genitalia are re-described and illustrated for all species.